SPE Europec Featured at 81st EAGE Conference and Exhibition 2019
DOI: 10.2118/195466-ms
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Models for Liquid Loading Prediction in Gas Wells

Abstract: Liquid loading phenomenon is known as the inability of the produced gas to carry all the co-produced liquid to the surface. Under such condition, the non-removed liquid accumulates at the wellbore resulting in reduction of the production and sometimes cause the death of the well. Several studies were carried out and correlation were developed based on field and experimental data with the aim to predict the onset of liquid loading in a gas well. However, each model provides different indication on the critical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…A 60 mm diameter test pipe was positioned at angles of 30 • , 45 • and 60 • from horizontal. The experiments showed that the liquid film model was in good agreement with the experimental results [9].…”
Section: Introductionsupporting
confidence: 73%
“…A 60 mm diameter test pipe was positioned at angles of 30 • , 45 • and 60 • from horizontal. The experiments showed that the liquid film model was in good agreement with the experimental results [9].…”
Section: Introductionsupporting
confidence: 73%
“…The maximum relative error is 8.73%, the minimum is 6.38%, and the errors are not more than 10%, indicating that the new model has high accuracy. The liquid-film reversal model is compared with 110 sets of laboratory experimental data in published literature [29][30][31][32][33][34][35][36][37]. The experiment data covers the pipe size range from 30 mm to 152 mm, with an inclination of 1 degree to 90 degrees.…”
Section: Verification Of the Prediction Model Of Critical Liquid-carrying Gas Velocitymentioning
confidence: 99%